miR-100-5p Downregulates mTOR to Suppress the Proliferation, Migration, and Invasion of Prostate Cancer Cells - Ye, Yun; Li, Su-Liang; Wang, Jian-Jun (Frontiers in Oncology, 2020)
Background Previous studies have shown that miR-100-5p expression is abnormal in prostate cancer. However, the role and regulatory mechanism of miR-100-5p requires further investigation. Thus, the aim of this study was to observe the effects of miR-100-5p on the proliferation, migration and invasion of prostate cancer (PCa) cells and to explore the potential related regulatory mechanism. Materials and Methods Differential miRNA expression analysis was performed using next-generation sequencing (NGS) in the patients with PCa and benign prostatic hyperplasia (BPH). The expression levels of miR-100-5p were detected using real-time fluorescence quantitative PCR (qRT-PCR). PCa cells were transfected with NC-mimics or miR-100-5p mimics, inhibitor by using liposome transfection. Moreover, the CCK-8 proliferation assay, colony formation assay, cell scratch assay and Transwell assay were used to detect the effects of miR-100-5p on cell proliferation, migration, and invasion. In addition, the target gene of miR-100-5p was verified by luciferase reporter gene assay, and the influence of miR-100-5p on the expression of mTOR mRNA by qRT-PCR and the expression of mammalian target of rapamycin (mTOR) protein was detected by western blot and immunohistochemical staining. Results Differential expression analysis of high-throughput sequencing data showed low expression of miR-100-5p in the patients of PCa. It was further confirmed by qRT-PCR that the expression of miR-100-5p in PCa cells was significantly lower than that in RWPE-1 cells (P<0.01). miR-100-5p expression in lymph node carcinoma of prostate(LNCaP) cells was markedly upregulated after transfection with miR-100-5p mimics (P<0.01), while cell proliferation, migration and invasion capacities were clearly reduced (P<0.01). mTOR mRNA and protein expression was also substantially lowered (P<0.01) and mTOR adjusted the expression of NOX4. Finally, we further confirmed by immunohistochemical staining that miR-100-5p regulated the expression of mTOR and NOX4. Conclusion miR-100-5p is expressed at low levels in PCa cells, and it can suppress PCa cell proliferation, migration and invasion, the mechanism of which is related to downregulating the expression of mTOR.